Pregnancy in women with thalassemia: challenges and solutions - Petrakos G; Andriopoulos P; Tsironi M (Dove Medical Press, 2016)
George Petrakos, Panagiotis Andriopoulos, Maria Tsironi Department of Nursing, University of Peloponnese, Sparta, Greece Abstract: Advances in treatment of thalassemia have led to the aging of thalassemic patients, and consequently concern about successful reproductive outcome is augmented. Although women with thalassemia intermedia only were considered competent of achieving pregnancy, case series reveal the willingness of both thalassemia major and thalassemia intermedia women to have a family. Pregnancy in general is characterized by dynamic multiple-system changes and increased susceptibility to oxidative stress, while homozygous, transfusion-dependent, β-thalassemia patients manifest cardiac, hepatic, endocrine, and metabolic disorders attributable to chronic anoxia and iron overload and thalassemia intermedia, usually nontransfused, is associated with augmented risk of thromboembolic events. Pregnancy in thalassemia should be considered a high risk for both mother and fetus, and favorable outcomes are the result of continuous preconception, antenatal, and postpartum assessment and management by a team of thalassemia experts. Keywords: thalassemia, pregnancy, chelation, transfusion, iron